A superstrate and FSS embedded dual band waveguide aperture array with improved far‐field characteristics. Issue 1 (24th October 2022) - Chandra, Avinash; Mishra, Naveen; Kumar, Rajkishor; Kumar, Kundan; Patil, Hemprasad Yashwant
Abstract: In this article, frequency selective surfaces (FSS) and superstrate embedded waveguide aperture arrays have been proposed. Three FSS are embedded in the transverse‐plane in WR‐90 waveguide and the unit superstrate cell is kept at a certain distance to achieve circular polarization. Optimization and analysis have been done by commercially available software Ansys HFSS 16.0. The proposed array has dual‐band behavior with input reflection coefficient ranges from 8.5 to 9.53 GHz and 10.15 to 10.49 GHz. Further analysis shows that the presented array has a higher gain as compared with the conventional open‐ended WR‐90 waveguide. In addition, the proposed array also provides low cross‐polarization and 5–6 dBi higher gain compared with the open WR‐90 waveguide array.